Prioritization of Green Logistics Activities using Fuzzy AHP-TOPSIS Approach - Mandal, Fatih Tevfik; Işık, Gürkan (Fevzullah TEMURTAŞ, 2025)
In today’s world, where environmental sustainability is gaining increasing importance, the green transformation of logistics processes has become a critical area both for achieving cost savings and for reducing environmental impacts. However, determining which green logistics activities should be prioritized is a complex issue due to uncertainties and the involvement of numerous criteria in the decision-making process. To address this complexity, a decision-making framework was developed in this study. First, based on a literature review, 12 main criteria influencing green logistics activities were identified, and the Fuzzy AHP and Fuzzy TOPSIS methods, as multi-criteria decision-making approaches, were integrated. The evaluations of decision-makers were collected using the linguistic fuzzy logic approach, and the weights of the criteria were calculated through the Fuzzy AHP method. In the second stage, green logistics activities were prioritized using the Fuzzy TOPSIS method, and it was determined that “creating environmental awareness” and “reducing waste” were the activities that should be addressed with the highest priority. This finding indicates that prioritizing environmental awareness as a first step represents a strategic approach for companies in their sustainability-oriented transformation processes. This study contributes to the literature as the first application conducted in Türkiye on the prioritization of green logistics activities.

Çevresel sürdürülebilirliğin giderek daha fazla önem kazandığı günümüzde lojistik süreçlerin yeşil dönüşümü hem maliyet tasarrufu sağlamak hem de çevresel etkileri azaltmak adına kritik bir alan haline gelmiştir. Ancak bu süreçte hangi yeşil lojistik faaliyetlerinin önceliklendirilmesi gerektiği konusu, belirsizlikler ve çok sayıda kriterin karar sürecine dahil olması nedeniyle karmaşık hale gelmektedir. Çalışmada, bu karmaşıklığa yeni bir çözüm açısı getirebilmek amacıyla bir karar süreci oluşturulmuştur. İlk olarak literatür taraması doğrultusunda yeşil lojistik faaliyetlerini etkileyen 12 ana kriter belirlenmiş ve çok kriterli karar verme yöntemlerinden Bulanık AHP ve Bulanık TOPSIS yöntemleri entegre şekilde kullanılmıştır. Karar vericilerin değerlendirmeleri dilsel bulanık mantık yaklaşımı ile toplanarak kriterlerin ağırlıkları Fuzzy AHP yöntemi ile hesaplanmıştır. İkinci aşamada, yeşil lojistik faaliyetleri Bulanık TOPSIS yöntemi ile önceliklendirilmiş, “çevresel farkındalık oluşturma” ve “atıkların azaltılması” faaliyetlerinin en öncelikli ele alınması gereken faaliyetler olduğu tespit edilmiştir. Bu durum, işletmelerin sürdürülebilirlik odaklı dönüşüm süreçlerinde ilk adım olarak çevresel farkındalık oluşturmaya öncelik vermelerinin stratejik bir yaklaşım olacağını göstermektedir. Bu çalışma, yeşil lojistik faaliyetlerinin önceliklendirilmesi ile ilgili Türkiye özelinde gerçekleştirilmiş ilk uygulama olarak literatüre katkı sunmaktadır.
Yeşil Lojistik Faaliyetlerinin Bulanık AHP-TOPSIS Yaklaşımı ile Önceliklendirilmesi
Keywords: Theory of Computation (Other); Hesaplama Teorisi (Diğer)